Health promotion interventions for the control of hypertension in Africa, a systematic scoping review from 2011 to 2021. - Jinhee Shin; Kennedy Diema Konlan; Eugenia Mensah (PLoS ONE)
Background A proportion of hypertension patients live in developing countries with low awareness, poor control capabilities, and limited health resources. Prevention and control of hypertension can be achieved by applying both targeted and population-based health promotion interventions. This study synthesised the health promotion interventions for the control of hypertension in Africa. Methods An in-depth search of PubMed, CINAHL, EMBASE, Cochrane library, web of science, google scholar yielded 646 titles and 615 after duplicates were removed. Full text (112) was screened, and ten articles were selected. The data analysis method was thematic analysis through the incorporation of convergent synthesis. The major sub-themes that were identified were reduction in the prevalence of hypertension, increase in knowledge, impact and feasibility, role in the reduction of risk factors, and the cost associated with health promotion interventions. Results Health promotion interventions led to a remarkable decrease in the prevalence of hypertension, increased knowledge and awareness in the intervention compared to the control groups. Community-based interventions were noted to have a positive impact on people's adoption of measures to reduce risk or identify early symptoms of hypertension. There was a significant relationship for the reduction in salt consumption, smoking, alcohol use, and increased physical activity after the administration of an intervention. Interventions using community health workers were cost-effective. Conclusion To sustain health promotion interventions and achieve control of hypertension especially in the long term, interventions must be culturally friendly and incorporate locally available resources in Africa.